MODEL TAI (TEAM – ASSISTED INDIVIDUALIZATION) MELALUI PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA EKONOMI - Sudarno, Sudarno; Wardani, Dewi Kusuma (Jurnal Inovasi Pendidikan, 2010)
The aims of this research are to know how to design and how to implement cooperative learning model, Team Assisted Individualization (TAI) through contextual approach in enhancing student's learning achievement of Economic Mathematics course on Economic Education Program FKIP UNS in academic year 2009/2010. Subjects were students attending Economic Mathematics course in the first semester. Data were collected in the form of information about student's learning outcomes including the scores of exercises and competency tests. Data were collected from various sources which include: (1) The informants, the teaching team and the students, (2) Places and events that were taking place at teaching learning process, and (3) documents including curriculum, syllabus, lesson plans, learning contracts and assessment books. Techniques used in collecting data are (1) Interviews (2) Observations (3) Test and (4) Documentation. The result of the research revealed that students showed liveliness and increasing learning achievement. Most students dare to express their opinions and become critic. 25 students (81%) had increased their skill in team collaboration, and four students (13%) showed adequate improvement. Besides, the result shows that the implementation of the action on the second cycle has been successful indicated by at least 80% of students have a minimum score, 70.